INTERNALISASI PROFIL PELAJAR PANCASILA DALAM TRADISI KEAGAMAAN MULUDHEN DI SEKOLAH DASAR MADURA - Dyah Puspitasari, Aditya; Tri Febrianto, Priyono; Maulidiya, Zamrotun (International Conference on Humanity Education and Society (ICHES), 2024)
Muludhen is a religious tradition of the Madurese people to commemorate the birth of the Prophet Muhammad SAW. The Muludhen tradition is carried out at all levels of society, including the school environment. Muludhen celebrations in Madurese schools have become a culture that exists from elementary to high school levels. The traditions inherent in Madurese society have values ​​that can be internalized in students' characters. This research aims to provide an in-depth discussion regarding the internalization of Pancasila student profile ​​through the Muludhen religious tradition in forming the character of elementary school students. This study employs qualitative descriptive method. Data collection techniques used include interviews, observation and documentation. This research shows that the muludhen religious tradition shapes the profile of Pancasila students on the elements of faith, devotion to God Almighty, and noble morals; global diversity; mutual cooperation; and independence. Through the routine of following Muludhen religious traditions since elementary school, students not only celebrate but can also interpret Muludhen traditions. Student participation in the Muludhen tradition celebration will instill student character that internalizes elements of the Pancasila student profile.